2017
DOI: 10.1088/2053-1583/aa8e71
|View full text |Cite
|
Sign up to set email alerts
|

Towards band structure and band offset engineering of monolayer Mo (1− x ) W ( x ) S 2 via Strain

Abstract: Semiconducting transition metal dichalcogenides (TMDs) demonstrate a wide range of optoelectronic properties due to their diverse elemental compositions, and are promising candidates for next-generation optoelectronics and energy harvesting devices. However, effective band offset engineering is required to implement practical structures with desirable functionalities. Here, we explore the pressure-induced band structure evolution of monolayer WS2 and Mo0.5W0.5S2 using hydrostatic compressive strain applied in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 75 publications
(102 reference statements)
3
18
0
Order By: Relevance
“…Overall bandgap change is quite monotonic with pressure and changes at dE gap / dP ≈ −35 meV GPa ‐1 . This value is much similar to other 2D inorganic excitonic semiconductors such as MoS 2 , MoSe 2 , and WSe 2 which is around −5 to −50 meV GPa ‐1 . Similar changes can also be traced from micro‐absorption measurements in Figure 4b.…”
Section: Summary Of Experimental and Theoretical Bandgap Values For 2supporting
confidence: 81%
“…Overall bandgap change is quite monotonic with pressure and changes at dE gap / dP ≈ −35 meV GPa ‐1 . This value is much similar to other 2D inorganic excitonic semiconductors such as MoS 2 , MoSe 2 , and WSe 2 which is around −5 to −50 meV GPa ‐1 . Similar changes can also be traced from micro‐absorption measurements in Figure 4b.…”
Section: Summary Of Experimental and Theoretical Bandgap Values For 2supporting
confidence: 81%
“…This result can be a good response to the variation of Mo (1– x ) W x S 2 over the entire pressure range. Similarly, Nayak et al 31 and Kim et al 34 found that the bandgaps of bulk MoS 2 , Mo 0.5 W 0.5 S 2 , as well as WS 2 decrease continuously, whereas those of the monolayer and bilayer increase initially and then monotonously decrease to zero at which the metallization occurs with increasing pressure in terms of experimental measurements and ab initio calculations. Interestingly, higher W composition in monolayer Mo (1– x ) W x S 2 contributes to a greater pressure-sensitivity of direct bandgap opening.…”
Section: Resultsmentioning
confidence: 81%
“…1922,24,26,27 On the other hand, the electronic properties have also been changed under hydrostatic pressure. 21,22,24,27,3134 Especially, the bandgap of bulk TMDs was found to be reduced consequently and to become metallic with increasing pressure, whereas the bandgap of the monolayer gradually increased in the small pressure range. 21,22,31,32 Importantly, the evolution of band structure combined modulation of composition and number of layers under hydrostatic pressure has gained an increased interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analogous to the case of composition-dependent band-gap tuning in conventional III-V semiconductor alloys [400][401][402][403], the band-structure and band-gap engineering of composition-tuned monolayer MoS 2 -based alloys is extremely promising for enabling 2D optoelectronic applications with tailored properties. Moreover, composition-engineering can be combined with techniques such as "pressure-engineering" to enable a wide variety of band-alignments in these 2D alloys, as shown in the case of Mo 1-x W x S 2 monolayers by Kim et al [404]. MoS2 and WS2 or MoS2 and MoSe2, respectively [388][389][390][391][392][393][394].…”
Section: Substitutional Doping Of 2d Mosmentioning
confidence: 99%